Analysis of Price, Product Quality, and Brand Image on the Purchase Decision of Honda Beat Motorcycles - Agnesia Novalinda Ramadhani; Taufiqurrahman Widyo Budi Saputra; Mashita Fahmi Wardhani (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
In January 2025, automatic motorcycles recorded a fantastic market share of 93.75% of total sales. This figure confirms Indonesian consumers' preference for the practicality and comfort offered by automatic motorcycles. This trend shows a shift in consumer interest, with consumers now preferring automatic motorcycles for their daily mobility needs over manual motorcycles. The purchase decision is a stage in the decision-making process until the consumer actually buys the product. Based on the background of the research through interviews, the researcher found that sales of Honda Beat motorcycles at the Taruna Adi Prima branch in Pati city fluctuated annually. Based on this background, the researcher was interested in determining the influence of price, product quality, and brand image on purchasing decisions. The number of respondents was 100 who had purchased Honda Beat motorcycles at the Taruna Adi Prima branch in Pati City, which became the sample for this quantitative study. Based on the research results, the price variable did not have an influence on purchasing decisions, but product quality had a positive and significant influence, and brand image also had a positive and significant influence with a significance value (sig) of 0.000 < 0.05.